2018
DOI: 10.1021/acsami.8b07001
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Hybrid a-SiOx(Mo) Layer for Hole-Selective and Interface Passivation of Highly Efficient MoOx/a-SiOx(Mo)/n-Si Heterojunction Photovoltaic Device

Abstract: The promising n-Si-based solar cell is constructed for the purpose of realizing hole- and electron-selective passivating contact, using a textured front indium tin oxide/MoO structure and a planar rear a-SiO/poly(Si(n)) structure severally. The simple MoO /n-Si heterojunction device obtains an efficiency of 16.7%. It is found that the accompanying ternary hybrid SiO(Mo) interlayer (3.5-4.0 nm) is formed at the MoO /n-Si boundary zone without preoxidation and is of amorphous structure, which is determined by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 36 publications
5
47
0
Order By: Relevance
“…At the interface with the Si, an amorphous interlayer of about 2 nm in thickness is observed in both cases. Such a layer was also reported in other studies [175] where energy-filtered TEM (EF-TEM) analysis revealed a composition of Si, O and Mo atoms, referred to as a hybrid a-SiO x (Mo) layer. The accompanying SiO x (Mo) interlayer, which is possibly formed during the deposition of MoO x on Si, could have multiple roles in the charge carrier transport in our devices such as passivating the Si surface, hence suppressing the electron current and inducing a hole inversion layer.…”
Section: Materials Analysissupporting
confidence: 82%
See 4 more Smart Citations
“…At the interface with the Si, an amorphous interlayer of about 2 nm in thickness is observed in both cases. Such a layer was also reported in other studies [175] where energy-filtered TEM (EF-TEM) analysis revealed a composition of Si, O and Mo atoms, referred to as a hybrid a-SiO x (Mo) layer. The accompanying SiO x (Mo) interlayer, which is possibly formed during the deposition of MoO x on Si, could have multiple roles in the charge carrier transport in our devices such as passivating the Si surface, hence suppressing the electron current and inducing a hole inversion layer.…”
Section: Materials Analysissupporting
confidence: 82%
“…The accompanying SiO x (Mo) interlayer, which is possibly formed during the deposition of MoO x on Si, could have multiple roles in the charge carrier transport in our devices such as passivating the Si surface, hence suppressing the electron current and inducing a hole inversion layer. Further, the sub-stiochiometric nature of the e-beam deposited MoO x thin films was confirmed by X-ray photoelectron spectroscopy (XPS) analysis (not shown) which indicates x=2.42±0.24 that is in close agreement with other reports [162,175]. The bipolar-mode diode characteristics of the MoO x based MnIS diodes as studied by electrical and light emission measurements will be treated in the following sections.…”
Section: Materials Analysissupporting
confidence: 82%
See 3 more Smart Citations